Stevia rebaudiana Bertoni: An alternative Sugar Replacer and Its Application in Food Industry - Gasmalla, Mohammed Abdalbasit A.; Yang, Ruijin; Hua, Xiao (Food engineering reviews, 2014)
Stevia rebaudiana Bertoni is a branched bushy shrub of the Asteraceae family, native to the Amambay region in the northeast of Paraguay. Stevioside and rebaudioside A are the main sweetening compounds of interest, which are commercially produced by both chemical and physical processes. S. rebaudiana has a great potential as a new agricultural crop since consumer demand for health promoting foods is increasing, and proximate analysis has shown that Stevia also contains substantial amounts of proteins, potassium, and other essential nutrients. Stevia can be taken in as a carbohydrate diet source without calories. This paper provides an overview of structure and properties of stevioside, various extraction techniques, applicability in food industry, and recent technological advances achieved.